An introduction to financial option valuation : mathematics, stochastics and computation - Higham, Desmond. J. (Cambridge : Cambridge University Press, 2004)
Provides a solid introduction to financial option valuation for undergraduate students armed with a working knowledge of first-year calculus. Written in a series of short chapters, its self-contained treatment gives equal weight to applied mathematics, stochastics and computational algorithms.
Includes bibliographical references and index.
oif 05/05/15
Loan
Keywords: Options (Finance) -- Valuation -- Mathematical models; Options (Finance) -- Prices -- Mathematical models; Derivative securities